Effect of helmet wear on the incidence of head/face and cervical spine injuries in young skiers and snowboarders - Macnab, A (BMJ Group, 2002)
Purpose: To evaluate whether helmets increase the incidence and/or severity of cervical spine injury; decrease the incidence of head injury; and/or increase the incidence of collisions (as a reflection of adverse effects on peripheral vision and/or auditory acuity) among young skiers and snowboarders. Methods: During one ski season (1998–99) at a world class ski resort, all young skiers and snowboarders (<13 years of age) presenting with head, face, or neck injury to the one central medical facility at the base of the mountain were identified. On presentation to the clinic, subjects or their parents completed a questionnaire reviewing their use of helmets and circumstances surrounding the injury event. Physicians documented the site and severity of injury, investigations, and disposition of each patient. Concurrently, counts were made at the entry to the ski area of the number of skiers and snowboarders wearing helmets. Results: Seventy children were evaluated at the clinic following ski/snowboard related head, neck, and face injuries. Fourteen did not require investigation or treatment. Of the remaining 56, 17 (30%) were wearing helmets and 39 (70%) were not. No serious neck injury occurred in either group. Using helmet-use data from the hill, among those under 13 years of age, failure to wear a helmet increased the risk of head, neck, or face injury (relative risk (RR) 2.24, 95% confidence interval (CI) 1.23 to 4.12). When corrected for activity, RR was 1.77 and 95% CI 0.98 to 3.19. There was no significant difference in the odds ratio for collisions. The two groups may have been different in terms of various relevant characteristics not evaluated. No separate analysis of catastrophic injuries was possible. Conclusion: This study suggests that, in skiers and snowboarders under 13 years of age, helmet use does not increase the incidence of cervical spine injury and does reduce the incidence of head injury requiring investigation and/or treatment.